Discourse on the Debate on Bawaslu's Authority in Handling Election Violations After the Determination of National Vote Results: - Satriya Nugraha (Universitas Bali Dwipa, 2023)
Violations in the electoral process in Indonesia are an issue that often occurs during the electoral process, where the Election Supervisory Body (Bawaslu) is tasked with preventing and taking action related to alleged election violations, not only during the election but also when the vote results have been determined nationally, with the hope of realizing a fair and integrity election. This study aims to describe the limitations of Bawaslu in carrying out its duties fully to oversee the entire series of elections following statutory regulations. This research uses a normative juridical research method through a statutory approach. The results of this study reveal that Bawaslu is unable to fully carry out its duties in taking action against alleged election violations after the determination of the vote until the stage of taking the oath or pledge because there is a legal vacuum in Article 93 letter d of Law Number 7 of 2017 concerning General Elections which outlines that Bawaslu is only tasked with overseeing the implementation of the election until the stage of determining the election results. Law Number 7/2017 on General Elections must be reviewed to provide legal certainty to Bawaslu in carrying out its duties under statutory regulations.